DEVELOPMENT OF THE TECHNIQUE INTRODUCTION OF THE BALL INTO THE GAME AT DIFFERENT POINTS WITH THE HELP OF SPECIAL EXERCISES (World Bulletin of Social Sciences, 2023)
This article will talk about the problems associated with the effectiveness of mastering the technique of introducing a partner to the game at different points of the table during the game and competitions of table tennis players using special exercises and ways to eliminate them, as well as the importance of improving physical fitness. from athletes